PROCESS-BASED LEARNING AND REFLECTION JOURNAL TO PROMOTE LEARNERS’ AUTONOMY IN STYLISTIC WRITING CLASS - Fransisca Kristanti (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
The main concern in education for the past decade has been on establishing autonomous learners. Giving more responsibility to learners in conducting the course of their learning is possible by applying appropriate approach and structured monitoring. In process-based learning, learners are motivated to experience a full cycle of writing process from planning to revision. What is more important is that learners are also encouraged to measure their development by keeping track of those processes in the form of reflection journal. While, the process-based learning enables learners to sharpen their cognitive awareness by exercising selfevaluation, peer-evaluation, and feedback-evaluation, the reflection journal enables them to evaluate and reflect their overall experience, including the difficulties they encounter during the processes. For this purpose, the reflection journal is designed as a tool which makes learners understand their initial and final strengths and weaknesses, their internal and external challenges and supports, and their past and future commitments autonomously with limited involvement from the teacher. In Stylistic Writing class, processbased learning and reflection journal are essential to establish learners’ autonomy in a way that they raise learners’ awareness of their own ability and needs as well as being sensitive to the issues in their environment. The combination of both helps learners identify pressing problems in their close environment and present solutions to those problems which leads to the creation of autonomous learners. Keywords: process-based learning, reflection journal, learners’ autonomy, stylistic writing